Bone Maturnity Delay in Congenital Hypothyroid - Azhari Gani; Iskandar Zakaria (Budapest International Research and Critics University, 2021)
Congenital hypothyroid (CH) is a Hormonal disorder that can be caused by thyroid gland dysfunction and if not treated early on, will cause serious mental and physical growth disorders. CH is divided into permanent and transient forms which etiologically can be divided into primary, secondary or peripheral. Thyroid dysgenesis is the primary cause and 85% of permanent CH is with abnormalities of thyroid hormone biosynthesis from birth (dishormongeneses). The incidence of dysgenesis accounts for 10-15% of cases. Transient congenital thyroid occurs mostly in infants with preterm birth in low-iodine endemic areas. A study showed a permanent incidence of CH 1: 1500 and transient CH 1: 300 in one of the areas with iodine deficiency in Central Java.Survival analysis showed that the risk of developing mental retardation and delayed physical growth was greater at the age of diagnosis over 1 year.